Instructional approaches and challenges of STEM instructional implementation: a systematic review - Ramli, Nur Farhana; Talib, Othman; Hassan, Siti Aishah; Abdul Manaf, Umi Kalthom (Faculty of Educational Studies, Universiti Putra Malaysia, 2017)
This study presents a systematic literature review of STEM instructional implementation. We consider factors such as publication year, learner type and challenges in the implementation. The full range of Scopus journals were surveyed and a total of 10 journal research articles were selected for the analysis. The findings reveal that a model based approach were the most used in STEM instructional approaches by STEM teachers followed by project based learning and problem based learning. Some noted challenges imposed in STEM instructional implementation such as teachers’ content knowledge, engagement activity, explanation session, confidence and evaluation, are discussed in detail. We conclude this review with come theoretical and methodological suggestions for future research.